Performance of Broilers Supplemented with Porang Glucomannan and Bacillus subtilis - Yenny Niken Larasati; Acep Perdinan (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2022)
The study was designed to evaluate the effect of porang glucomannan andBacillus subtilis on the performance of broiler chickens. One hundred and sixty dayold chick of broilers were kept for 5 weeks with average body weight 42.6 ± 2.9gram. The experiment was arranged as a completely randomized design with 4treatments and 4 replications. The treatments were T0 (control), T1(supplementation of prebiotic porang glucomannan), T2 (supplementation ofprobiotic Bacillus subtilis), and T3 (supplementation of synbiotic porangglucomannan and Bacillus subtilis). Parameters measured were body weight, feedintake, and feed conversion ratio (FCR). Overall body weight in treatments T1, T2,and T3 were greater (p<0.05) than T0. Moreover, FCR of T1, T2, and T3 were lower(p<0.05) than T0. However, there was no effect of dietary treatments on feed intake.It was concluded that supplementation of porang glucomannan and/ or Bacillussubtilis increased body weight and decreased feed conversion ratio than controlwithout any negative effect of dietary treatments on feed intake of broilers.